Ecoclimatic modification of Delhi due to urbanization - PADMANABHAMURTY, B.; BAHL, H. D. (MAUSAM, 1981)
Temperature, humidity and wind fields at the surface over Delhi during winter period are presented. The temperature analysis suggests several warm pockets and cold pools. The humidity field indicates an inverse relation with temperature except close to water surfaces or green vegetation. Wind fields tend to be anticyclonic. Climograms for urban and rural Delhi point out the differences in comfort at both the localities. During daytime rural Delhi is comfortable in February, March and December but at urban Delhi January, February and December are comfortable. Similarly, during nighttime while rural Delhi is comfortable in May and June only, urban Delhi is comfortable in April, October and November. Remaining months in each case are uncomfortable either on the hotter side or colder side.